Örgüt Kültürünün Örgütsel Yabancılaşmaya Etkisi Örgütsel Güvenin Aracılık Rolü - Kahveci, Gökhan; Demirtaş, Zülfü (Fırat University, 2014)
Bu araştırmanın amacı; öğretmenlerin Örgüt Kültürü, Örgütsel Güven ve Örgütsel Yabancılaşma değişkenlerine ilişkin algıları arasındaki etki düzeyleri ve bu değişkenlerin birbirini nasıl yordadıkları ve açıklama oranlarının ne düzeyde olduğunu belirlemektir. Araştırma ilişkisel tarama modelinde tasarlanmıştır. Araştırmanın örneklemini 2013-2014 eğitim öğretim yılında Rize ili merkez ve tüm ilçelerinde bulunan ilkokul, ortaokul ve liselerde görev yapmakta olan 2219 öğretmen oluşturmaktadır. Araştırmada veri toplama aracı olarak Demirtaş ve Ekmekyapar’ın (2012) Örgüt Kültürü, Yılmaz’ın (2005) Örgütsel Güven ve Eryılmaz’ın (2010) geliştirdiği Örgütsel Yabancılaşma ölçekleri kullanılmıştır. Araştırmada öğretmenlerin demografik özelliklerine ilişkin frekans ve yüzde değerleri hesaplanmıştır. Bunun yanında araştırmanın değişkenleri olan Örgüt Kültürü, Örgütsel Güven ve Örgütsel Yabancılaşma arasındaki ilişkiyi belirlemek amacıyla Yapısal Eşitlik Modellemesi yapılmıştır. Araştırma sonucunda, Örgüt Kültürünün Örgütsel Yabancılaşmayı olumsuz; Örgütsel Güveni olumlu yönde anlamlı şekilde yordadığı görülmüştür. Bunun yanında Örgütsel Güvenin Örgütsel Yabancılaşmayı olumsuz yönde anlamlı şekilde yordadığı sonucuna ulaşılmıştır. Ayrıca Örgüt Kültürü ile Örgütsel Yabancılaşma arasında Örgütsel Güvenin kısmi aracılık etkisinin olduğu belirlenmiştir.

The purpose of this study is to determine effect levels between teachers’ perceptions regarding organizational culture, organizational trust and organizational alienation variables and to determine their predictions about these variables and levels of accountability. The research is based on relational screening model. The sample group is consisted of 2219 teachers who worked for primary, secondary and high schools located in Rize town center and all counties during 2013 – 2014 school year. organizational culture scale developed by Demirtaş and Ekmekyapar (2012), organizational trust scale developed by Yılmaz (2005) and organizational alienation scale developed by Eryılmaz (2010) are used as data collection tools on the research. The study also calculated frequency and percentage values regarding demographic properties of the teachers. Furthermore, structural equation modeling is used for the purpose of determining the relationship between variables of the study, namely organizational culture, organizational trust and organizational alienation. The results of this study revealed that organizational culture has negative predictions about organizational alienation and positive as well as significant predictions about organizational trust. Besides, it is determined that organizational trust has negative and significant predictions about organizational alienation. Inaddition to organizational trust has partial mediating effect between organizational culture and organizational alienation.
The Effects of Organizational Cultures on Organizational Alienation: Mediating Role of Organizational Trust